One-step preparation of silver nanoparticle containing polymer nanocomposites via stereolithography technique - Baykal, Ayberk; Aksan, Onur Alp; Oral, Ahmet Yavuz; Bilge, Kaan; Kızıldağ, Nuray (İdris Karagöz, 2024)
As a technique that uses ultraviolet light to cure photo-polymers layer by layer with high spatial resolution and surface quality, stereolithography (SLA) allows for precise process control and optimization for various UV-curable polymers and their nanocomposites with various nanoparticles. In this study, UV-curable polymer nanocomposites were prepared with the addition of different contents of silver nitrate via SLA technique for use in antibacterial applications. In-situ synthesis of AgNPs was achieved during the SLA process without any additional treatments. The effect of AgNO3 addition on the curing of the resin and the mechanical properties of the nanocomposite specimens were investigated. To understand the fracture mechanism of the nanocomposite samples, the fractured surfaces of the samples were evaluated by SEM, and the AgNO3 content of the nanocomposite was evaluated by EDX. The nanocomposites containing 0.3 wt. % AgNO3 exhibited improved mechanical properties. Further increasing the AgNO3 content to 3 wt. % led to deterioration in the physical and mechanical properties of the polymer nanocomposites.

As a technique that uses ultraviolet light to cure photo-polymers layer by layer with high spatial resolution and surface quality, stereolithography (SLA) allows for precise process control and optimization for various UV-curable polymers and their nanocomposites with various nanoparticles. In this study, UV-curable polymer nanocomposites were prepared with the addition of different contents of silver nitrate via SLA technique for use in antibacterial applications. In-situ synthesis of AgNPs was achieved during the SLA process without any additional treatments. The effect of AgNO3 addition on the curing of the resin and the mechanical properties of the nanocomposite specimens were investigated. To understand the fracture mechanism of the nanocomposite samples, the fractured surfaces of the samples were evaluated by SEM, and the AgNO3 content of the nanocomposite was evaluated by EDX. The nanocomposites containing 0.3 wt. % AgNO3 exhibited improved mechanical properties. Further increasing the AgNO3 content to 3 wt. % led to deterioration in the physical and mechanical properties of the polymer nanocomposites.
Sterolitografi tekniği ile tek adımda gümüş nanopartikül içeren nanokompozitlerin hazırlanması
GTU-BAP Project 2023-A-101-15
Keywords: Functional Materials; Fonksiyonel Malzemeler [EN] Composite and Hybrid Materials; Kompozit ve Hibrit Malzemeler [EN] Polymers and Plastics; Polimerler ve Plastikler